2016
DOI: 10.1016/j.biopsycho.2015.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Experienced stress produces inhibitory deficits in old adults’ Flanker task performance: First evidence for lifetime stress effects beyond memory

Abstract: Highlights AbstractStudies regarding aged individuals' performance on the Flanker task differ with respect to reporting impaired or intact executive control. Past work has explained this discrepancy by hypothesising that elderly individuals use increased top-down control mechanisms advantageous to Flanker performance. This study investigated this mechanism, focussing on cumulative experienced stress as a factor that may impact on its execution, thereby leading to impaired performance. Thirty elderly and thirty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 69 publications
2
15
0
Order By: Relevance
“…These findings highlight the damaging effect of cumulative lifetime stress, which emerges in later life and accelerates senescence in old adults. Our own work extended these behavioral findings by demonstrating that they coincide with task dependent alterations in the theta, alpha and upper gamma frequencies (Marshall et al, 2015;Marshall et al, 2016aMarshall et al, , 2016b.…”
Section: Cumulative Life Stress and Cognitive Agingsupporting
confidence: 63%
See 1 more Smart Citation
“…These findings highlight the damaging effect of cumulative lifetime stress, which emerges in later life and accelerates senescence in old adults. Our own work extended these behavioral findings by demonstrating that they coincide with task dependent alterations in the theta, alpha and upper gamma frequencies (Marshall et al, 2015;Marshall et al, 2016aMarshall et al, , 2016b.…”
Section: Cumulative Life Stress and Cognitive Agingsupporting
confidence: 63%
“…For example, we recently demonstrated that among old adults, stress-related reductions of memory performance coincided with reduced upper gamma activity (Marshall et al, 2015) while executive impairments correlated with reduced synchronisation of the alpha rhythm (Marshall et al, 2016a). Our findings thus highlight that cumulative stress impacts on cortical neurocognitive processes necessary for intact cognitive performance.…”
Section: Cumulative Life Stress and Cognitive Agingmentioning
confidence: 52%
“…Several hypotheses have been proposed emphasizing the possible relationship between these deficits and a progressive degeneration of the prefrontal cortex (Hedden and Gabrieli, 2004; Gazzaley et al, 2008). In addition and especially relevant to the current issue, previous studies have reported that the aging population displays a reduced ability to make appropriate decisions and to choose between conflicting alternatives (Vallesi and Stuss, 2010; Korsch et al, 2014; Marshall et al, 2016), a function that requires a tight interaction between cognition and action and thus also relies on prefrontal functioning (Hedden and Gabrieli, 2004, 2005). Interestingly, it has been proposed that the aging brain progressively loses its capacity to suppress irrelevant information (Eriksen and Eriksen, 1974; Radvansky et al, 2005; Lucci et al, 2013; Korsch et al, 2016), resulting in an overflow of inappropriate neural activity which in turn, interferes with the processing of pertinent information (Gazzaley et al, 2008; Zhu et al, 2010).…”
Section: Introductionmentioning
confidence: 95%
“…In addition to experiencing reduced social networks and social support, migrants are often under great stress during the migration process [ 62 , 63 ]. Studies have shown that stressful life events may affect elderly participants' inhibitory control in attentional and sensorimotor domains and therefore influence their cognitive function [ 64 ]. However, a longer stay in a hosting place has been shown to be associated with less stress and an improved social network [ 65 ].…”
Section: Potential Mechanisms Impacting Relationships Between Migratimentioning
confidence: 99%